Effectiveness of science learning materials based guided discovery model to improve science process skills - Y A Imran; R Agustini; T Taufikurohmah (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The curriculum 2013is developed with the refinement of teacher centered learning into student centered learning.The learning design in thecurriculum 2013 is emphasized on the application of science process skills. Based on premilinary study in junior high school, the science process skills of the students is weak. Therefore, teacher must practice science process skills to students with suitable learning model. One of learning model that suitable to practice science process skills is guided discovery model. The purposes of this research is to describe the effectiveness science learning materials based guided discovery model to improve science process skills. The effectiveness of learning materials is reviewed from science process skills of the students and student response. The development research method using 4D model. The process of developing science learning material starts from defining step, the process of designing the learning material developed based on information obtained from the step of early analysis, learners, materials, tasks that support then done the design step or design, then the last step is the development step. Based on the result of the research, it is found that science process skills of the students are improved and the students gived a positive response after learning with the learning material based guided discovery model. It is conclude that, science learning materials based guided discovery model is effective to improve science process skills.